Comparative transcriptomic analysis of normal and abnormal in vitro flowers in Cymbidium nanulum Y. S. Wu et S. C. Chen identifies differentially expressed genes and candidate genes involved in flower formation - Fu, Shuangbin; Yang, Yanping; Wang, Peilong; Ying, Zhen; Xu, Wan; Zhou, Zhuang (Frontiers in Plant Science, 2022)
It is beneficial for breeding and boosting the flower value of ornamental plants such as orchids, which can take several years of growth before blooming. Over the past few years, in vitro flowering of Cymbidium nanulum Y. S. Wu et S. C. Chen has been successfully induced; nevertheless, the production of many abnormal flowers has considerably limited the efficiency of this technique. We carried out transcriptomic analysis between normal and abnormal in vitro flowers, each with four organs, to investigate key genes and differentially expressed genes (DEGs) and to gain a comprehensive perspective on the formation of abnormal flowers. Thirty-six DEGs significantly enriched in plant hormone signal transduction, and photosynthesis-antenna proteins pathways were identified as key genes. Their broad upregulation and several altered transcription factors (TFs), including 11 MADS-box genes, may contribute to the deformity of in vitro flowers. By the use of weighted geneco−expression network analysis (WGCNA), three hub genes, including one unknown gene, mitochondrial calcium uniporter (MCU) and harpin-induced gene 1/nonrace-specific disease resistance gene 1 (NDR1/HIN1-Like) were identified that might play important roles in floral organ formation. The data presented in our study may serve as a comprehensive resource for understanding the regulatory mechanisms underlying flower and floral organ formation of C. nanulum Y. S. Wu et S. C. Chen in vitro.